KOMUNIKASI PEMASARAN TERPADU (INTEGRATED MARKETING COMMUNICATION) DALAM MEMPROMOSIKAN DESTINASI WISATA ASIA FARM DI PEKANBARU - Siswoyo, Irwan; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Asia Farm is a new tourist destination in Pekanbaru that is very interesting to be used as a tourist visit. The existence of Asia Farm tourism began to be built at the end of 2018, but on April 21, 2019 was only officially opened to the public. Increasing the number of visitors requires effective integrated marketing communication to create attraction. The purpose of this study was to determine the segmentation, targeting, and positioning of Asia Farm in increasing tourist visits to Asia Farm tourist destinations, to find out the application of Integrated Marketing Communication Integrated Marketing Communication conducted by managers of Asia Farm in Pekanbaru.               This study used qualitative research methods. The subjects in this study consisted of eight subjects as informants through purposive techniques. Data collection techniques are grouped into three parts, namely: observation, interview and documentation. Data analysis techniques in this study used the interactive data model of Miles and Hiberman. Checking the validity of the data uses an extension and triangulation technique.            The results showed that the segmentation of Asia Farm managers was students with a target of 10,000 visitors per month and postioning in the form of the tag line "Asia Farm Hay Day". The form of integrated marketing communication Integrated Marketing Communication conducted by Asia Farm is interactive communication (online marketing), Asia Farm uses social media such as Instagram and Facebook as a promotional tool, personal selling, Asia Farm sends a team to do direct promotion to schools, sales promotion, which offers discounts and discounts to groups who buy tickets for more than 35 adults or for school children get a discount of Rp. 5000 per child. advertising, asia farm utilizes print and online media as well as billboards, banners and brochures to promote asia farm tourism. event, Asia Farm uses two events namely enterten event and educational event. word of mouth, the manager conveys information to the closest person and the person conveys it to others. and public relations, which is collaborating with travel journalists and bloggers in promoting Asia Farm.